2017
DOI: 10.1186/s40780-017-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Objective evaluation of chemotherapy-induced peripheral neuropathy using quantitative pain measurement system (Pain Vision®), a pilot study

Abstract: BackgroundIn an evaluation of chemotherapy-induced peripheral neuropathy (CIPN), objectivity may be poor because the evaluation is determined by the patient’s subjective assessment. In such cases, management of neuropathy may be delayed and CIPN symptoms may become severe. In this pilot study, we attempted an objective evaluation of CIPN using a quantitative pain measurement system (Pain Vision®).MethodsThe subjects were patients with gynecologic cancer who underwent chemotherapy using taxane and platinum drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Although an evaluation method that can quantify CIPN enables interindividual and intraindividual comparison, Sato et al . reported that there was no significant difference between PV and CTCAE grades in the evaluation of CIPN 42 . If the severity of CIPN and PV do not correlate, PV cannot be used to evaluate clinical trials aimed at improving CIPN.…”
Section: Discussionmentioning
confidence: 96%
“…Although an evaluation method that can quantify CIPN enables interindividual and intraindividual comparison, Sato et al . reported that there was no significant difference between PV and CTCAE grades in the evaluation of CIPN 42 . If the severity of CIPN and PV do not correlate, PV cannot be used to evaluate clinical trials aimed at improving CIPN.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the device could be used to compare disease severity among patients and to assess individual patient neurological conditions before and after treatment, which may not be possible with conventional sensory tests. PainVision ® has been previously employed in clinical practice to evaluate peripheral neuropathy, low back pain, and postherpetic neuralgia 15,18,25) ; however, it has not been used to measure sensory deficits in patients with cervical myelopathy. Our results reveal that PainVision ® can provide objective, quantitative data that are useful for determining neurological levels, as evidenced by the good correlation of CPT measurements with the functional status and the level of cervical cord compression revealed by MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Because CIPN manifests at the tip of the limbs, some may wonder whether PV measurement may be performed on the ulnar side of the forearms or at the tip of the limbs. Sato et al evaluated data from finger tips obtained from 41 patients, of which 28 manifested CIPN, and concluded that CIPN may be objectively evaluated by lowering the pain threshold using noninvasive and easy‐to‐use PV. Our present data show that further consideration is necessary at this point with regard to CIPN evaluation through the use of PV at the finger tips.…”
Section: Discussionmentioning
confidence: 99%